2016
DOI: 10.1016/j.bbamem.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces ordered domains formation in biomembranes: Implication for its pleiotropic action

Abstract: Resveratrol is a polyphenol compound with great value in cancer therapy, cardiovascular protection, and neurodegenerative disorders. The mechanism by which resveratrol exerts such pleiotropic effects is not yet clear and there is a huge need to understand the influence of this compound on the regulation of lipid domains formation on membrane structure. The aim of the present study was to reveal potential molecular interactions between resveratrol and lipid rafts found in cell membranes by means of Förster reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 60 publications
3
33
1
Order By: Relevance
“…Effects of RSV on Ca 2+ channels and signaling [ 44 , 45 ] and K + channels [ 46 , 47 ] have already been described in several studies. One link between the formation of AKAP/PKA signaling complexes and RSV may be the association of AKAPs and adenylate cyclase with lipid rafts [ 40 , 48 ] and the ability of RSV to influence the properties of bio membranes including lipid raft formation [ 33 , 34 , 35 ]. We investigated whether RSV changes the association of intestinal nutrient transporters with DRMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of RSV on Ca 2+ channels and signaling [ 44 , 45 ] and K + channels [ 46 , 47 ] have already been described in several studies. One link between the formation of AKAP/PKA signaling complexes and RSV may be the association of AKAPs and adenylate cyclase with lipid rafts [ 40 , 48 ] and the ability of RSV to influence the properties of bio membranes including lipid raft formation [ 33 , 34 , 35 ]. We investigated whether RSV changes the association of intestinal nutrient transporters with DRMs.…”
Section: Resultsmentioning
confidence: 99%
“…3. Since Resveratrol is known to affect membrane properties and influences the formation of detergent resistant membrane fractions (DRM) [ 32 , 35 ], the association of nutrient transport proteins with DRMS and therefore their activity may be changed by Resveratrol.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The position of resveratrol within the bilayer has also been discussed as concentration dependent 18 . Besides the location, the effects of resveratrol on the structure and fluidity of the lipid bilayer, it has been reported that resveratrol resembles cholesterol action on DMPC membrane and membrane models consisting of a mixture of egg-phosphatidyl choline, cholesterol, and sphingomyelin 6 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous studies have recently focused on the potential effects of natural compounds, including nutraceuticals, to halt the progression of OA and reduce any associated symptoms (Hussain et al, 2009;Moura et al, 2016). Resveratrol is a natural polyphenol extracted from Polygonum cuspidatum, which shows pleiotropic properties that suggest it may be applied for many therapeutic uses, including the treatment of cancer, cardiovascular diseases, and metabolic disorders (Neves, Nunes, Reis, 2016). Meanwhile, many preclinical studies have revealed the anti-inflammatory properties of resveratrol that might enable the degenerative articular damage to be ameliorated in vitro and in experimental animals (Jiang et al, 2017;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%